2022
DOI: 10.1002/ppul.26031
|View full text |Cite
|
Sign up to set email alerts
|

Early lung ultrasound score to predict noninvasive ventilation needing in neonates from 33 weeks of gestational age: A multicentric study

Abstract: Objective To propose an early lung ultrasound (LUS) score for the prediction of the need for respiratory assistance in newborns of gestational age (GA) ≥ 33 weeks presenting respiratory distress. Study Design and Setting Multicenter, prospective observational study in third‐level neonatal intensive care units. Patient Selection Infants with GA ≥ 33 + 0 weeks with respiratory distress within 3 h of life. Methods Three LUS for each patient were collected: within 3 h of life (T0), at 4–6 h of life (T1), and at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…After reading the titles, abstracts and full texts of the 518 related articles, a total of 10 eligible studies with 1162 participants were included. [ 9 , 15 , 17 20 , 22 24 , 26 ] The flow diagram for study selection is shown in Fig 1 . Some of the studies that were excluded for varying reasons are summarized in S1 Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the titles, abstracts and full texts of the 518 related articles, a total of 10 eligible studies with 1162 participants were included. [ 9 , 15 , 17 20 , 22 24 , 26 ] The flow diagram for study selection is shown in Fig 1 . Some of the studies that were excluded for varying reasons are summarized in S1 Table .…”
Section: Resultsmentioning
confidence: 99%
“…The other 3 articles [ 15 , 18 , 24 ] did not clearly state which guidelines were used for designing the standards for surfactant use but still highlighted the need to focus on ventilator parameters such as FiO2 and SpO2. With regards to the diagnostic criteria for lung ultrasound, 9 articles [ 9 , 15 , 17 , 18 , 20 , 22 24 , 26 ] employed the 3-region 18-point scoring system established by Brat et al [ 9 ] in evaluating the lung ultrasound results. One article [ 19 ] performed qualitative evaluation by classifying lung ultrasound images into different types based on A-line and B-line distribution [ 11 ] but did not provide the diagnostic data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perri et al 7 reported a study using a previously described LUS from Brat et al 9 and a descriptive score of the predominant LU pattern 10 (and both of these papers have good examples for beginning learners) to examine the need for noninvasive respiratory support (primarily continuous positive airway pressure (CPAP) and surfactant use. Using the Brat score, each lung is divided into three regions and assigned a score of 0–3.…”
Section: Progress In Neonatal Lung Ultrasound (Lu)mentioning
confidence: 99%
“…LUS scores obtained during the first days of life can provide information about the prognosis of neonatal respiratory failure ( 154 ) and predict the need for respiratory support ( 155 157 ). In addition, LUS performs a useful role in predicting non-invasive ventilation failure in neonates with respiratory distress, and this is important for the clinician to decide to apply invasive mechanical ventilation to prevent clinical deterioration ( 154 , 158 160 ).…”
Section: Other Applications Beyond Diagnosismentioning
confidence: 99%